Ritual Instructions in the Series Lamaštu - Barkowsky, Marie (My University, 2024)
The ritual series Lamaštu contains two sets of ritual instructions – ritual instructions written in rubrics after the text of an incantation on the first two Tablets of the series (Lam. I–II) and ritual instructions written on the ritual tablet (Lam. III). The two sets are partially overlapping, with long text passages in the rubrics having direct parallels on Lam. III; however, the order of the ritual instructions is very different. How, then, do they relate and how are they supposed to be used? As there are manuscripts that contain Lam. I–III – thereby including rubrics and ritual instructions – the difference in order cannot be attributed to different text recensions. The following article argues that the two sets of ritual instructions were intended to be complementary, and that neither can be used entirely on its own.
PUBLISHED